ANALISIS PENGARUH CITRA MEREK, KUALITAS PRODUK DAN HARGA TERHADAP NILAI PELANGGAN SERTA DAMPAKNYA PADA LOYALITAS PELANGGAN (Studi Pada Pelanggan Minuman Isotonik Pocari Sweat di Kota Pontianak) - admin, DEWI SHINTA B11112130 (Jurnal Manajemen Update, 2016)
This reseacrh aims for test and analyze the influence of brand image, product quality, and price of customer value isotonic water Pocari Sweat in Pontianak. This reseacrh is quantitative. Population of the research are pontianak all of isotonic water consumer and buyer. The sampel of 100 respondents, sampling technique that is used in this research is purposive sampling and then the data was processed by path analysis. The results of analysis for the first model show that brand image and price have a significant effect on customer value, think have no effect on customer value. Predictive capability of the three variabels on customer value is 32,8% while the remaining 67,2% was influenced by other factors not included in the research model. The results of analysis for the second model show that customer value have a significant effect on customers loyalty. Predictive capability of the variabel on customer loyalty is 39,4% while the remaining 60,6% was influenced by other factors not included in the research model. Keywords: brand image, product quality, price, customer value, customer loyalty